Predictor Factors of Multi-Drug Resistance Tuberculose on the Characteristics of Chest Radiographic Lesions - Ana Majdawati; Inayati Habib (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
This research aimed to demonstrate some predictors of screening diagnosis of multi-drug-resistant tuberculosis (MDR-TB). Researchers determined several predictors as a screening diagnosis of MDR-TB, based on clinical symptoms, WHO criteria, chest radiographic lesions, and sputum smear microscopy. The method demonstrated a correlation between several factors as predictors of the MDR-TB diagnosis consisting of clinical symptoms, WHO criteria, BTA sputum, and cross-sectional chest radiograph lesions, based on examination of Gene X-pert for suspected MDR-TB. The results demonstrated a significant and positive odds ratio value of the relationship between variables: 1). Clinical symptoms (p:0.000) with the largest percentage of coughing with shortness of breath exhibiting 51.32% and coughing exhibiting 27.9%; 2). WHO criteria are among others, new patients (p:0.000; OR:3); 3). Chest radiographic lesion: consolidation (p: 0.000; OR: 3); pleural thickening (p:0.003; OR:2); Fibrosis (p:0.000; OR:6) with location on the medial right (p:0.000; OR:2) and left inferior (p:0.000; OR:3). The BTA sputum is (p:0.000; OR:8). The predictors for screening the diagnosis of MDR-TB are coughing, and shortness of breath. Other WHO criteria include radiographic lesions, fibrosis, consolidation, pleural thickening with the location of lesions either left inferior or medial right and positive smear sputum results.Â